Relationships between blood bone metabolic biomarkers and anemia in patients with chronic kidney disease - Fan Li; Xiaoxue Ye; Guang Yang; Hui Huang; Anning Bian; Changying Xing; Shaowen Tang; Jing Zhang; Yao Jiang; Huimin Chen; Caixia Yin; Lina Zhang; et al. (Renal Failure)
Introduction Blood bone metabolic biomarkers are noninvasive indices for evaluating metabolic bone diseases. We investigated the relationships between blood bone metabolic biomarkers and anemia in chronic kidney disease (CKD) patients and analyzed the effects of parathyroidectomy (PTX) on the above indices.Methods In this cross-sectional study, 100 healthy controls and 239 CKD patients, including 46 secondary hyperparathyroidism (SHPT) patients with PTX, were enrolled. Moreover, a prospective study was conducted in which 28 PTX patients were followed up. The degree of anemia was classified as mild, moderate, or severe based on the tertiles of hemoglobin (Hb) levels of the anemic CKD patients, with cutoff values of 83 g/L and 102 g/L. Bone metabolic biomarkers, including calcium (Ca), phosphorus (P), intact parathyroid hormone (iPTH), fibroblast growth factor 23 (FGF23), and α-klotho, were tested.Results The mean estimated glomerular filtration rate (eGFR) in CKD patients was 25.7 ± 36.0 ml/min/1.73 m2, and 84.10% of CKD patients had anemia. The baseline Hb levels in the mild, moderate, and severe anemia subgroups were 110.86 ± 5.99 g/L, 92.71 ± 5.96 g/L, and 67.38 ± 10.56 g/L, respectively. CKD patients had higher adjusted Ca, P, alkaline phosphatase (ALP), iPTH, and FGF23 levels and lower α-klotho levels than controls. Baseline adjusted Ca, P, iPTH, and α-klotho levels were associated with Hb levels in CKD patients. Blood adjusted Ca, P, and iPTH levels were correlated with anemia severity. After PTX (median interval: 6.88 months), anemia and high blood adjusted Ca, P, iPTH, and FGF23 levels were ameliorated, while α-klotho levels were increased.Conclusions Blood adjusted Ca, P, iPTH, and α-klotho levels were correlated with Hb levels in CKD patients. Correction of bone metabolic disorders may be a therapeutic strategy for anemia treatment.